Conjuring, expanding, and blurring boundaries of sexual subcultures: the grounding of the fluid - Deshotels, Tina Hebert (Deviant behavior, 2020)
This paper creates a fluid model with which to research the connection between sexual subcultures and online spaces, as well as, the impact of online spaces on the creation and proliferation of sexual subcultures. This model is influenced by previous models that examined sexuality, both pre-internet and post. We offer an updated model that focues on, sexual subcultures in online spaces. A discussion of how this new model can be used to accommodate research on sexual subcultures in online spaces is offered.